1983
DOI: 10.1152/jappl.1983.55.3.1031
|View full text |Cite
|
Sign up to set email alerts
|

Single-position calibration of the respiratory inductance plethysmograph

Abstract: Since we intended to use the respiratory inductance plethysmograph (RIP) to study breathing patterns in a single body position, we developed a method to calibrate the RIP in one position (seated) and verified the stability of this calibration procedure during a 60-min period. The subject breathed spontaneously through a pneumotachograph for 1 min during all calibration and verification runs. All inspiratory data from the abdomen and rib cage RIP transducers was analyzed using multiple linear regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…Respiratory signals (tidal volume, rib cage and abdominal signals) were sampled at a rate of 20 signals·s -1 . The coefficients of rib cage and abdominal signals over a period of 5 min were derived from multiple linear regression (MLR) [22]. The accuracy of this method for estimation of tidal volume (VT) was checked by comparison with the mean VT value obtained simultaneously from the pneumotachograph.…”
Section: Methodsmentioning
confidence: 99%
“…Respiratory signals (tidal volume, rib cage and abdominal signals) were sampled at a rate of 20 signals·s -1 . The coefficients of rib cage and abdominal signals over a period of 5 min were derived from multiple linear regression (MLR) [22]. The accuracy of this method for estimation of tidal volume (VT) was checked by comparison with the mean VT value obtained simultaneously from the pneumotachograph.…”
Section: Methodsmentioning
confidence: 99%
“…of the Respitrace. The regression coefficients of the latter outputs can then be used to reconstruct the volume signal~Loveridge, West, Anthonisen, & Kryger, 1983!. The calibration should be repeated every time body posture is even slightly changed.…”
Section: Inductive Plethysmography (Respitrace)mentioning
confidence: 99%
“…It was subsequently confirmed that a linear combination of RIP ribcage and abdomen signals was indeed proportional to V T [5,6].…”
Section: Introductionmentioning
confidence: 77%